Literature Review : Faktor - Faktor yang Berpengaruh Terhadap Kejadian Demam Tifoid di Indonesia - Renitta Anggraeni; Tri Umiana Soleha; Rani Himayani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Typhoid fever is an endemic disease in Indonesia caused by Salmonella typhi bacteria and transmitted through the fecal-oral route. It remains a major public health issue with a relatively high prevalence rate. This study aims to identify the various factors influencing the incidence of typhoid fever in Indonesia through a literature review of scientific articles published between 2015 and 2025. A total of 10 articles were selected based on predefined inclusion criteria. The analysis revealed that the most prominent contributing factors include poor environmental sanitation, inadequate personal hygiene, a history of typhoid fever, and the habit of consuming food from street vendors. Understanding these factors is expected to enhance the effectiveness of disease prevention and control strategies.